2022
DOI: 10.1101/2022.08.31.505996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-intrinsic ceramides determine T cell function during melanoma progression

Abstract: Acid sphingomyelinase (Asm) and acid ceramidase (Ac) are parts of the sphingolipid metabolism. Asm hydrolyzes sphingomyelin to ceramide, which is further metabolized to sphingosine by Ac. Ceramide generates ceramide-enriched platforms that are involved in receptor clustering within cellular membranes. However, the impact of cell intrinsic ceramide on T cell function is not well characterized. By using T cell-specific Asm- or Ac-deficient mice, with reduced or elevated ceramide levels in T cells, we identified … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A recent study using T cell-specific acid sphingomyelinase-or acid ceramidase-deficient mice revealed that T cell-specific ablation of acid sphingomyelinase resulted in reduced ceramide levels in T cells and an impairment of T cell responses, whereas T cell specific deletion of the acid ceramidase elevated T cell activation (98). Decreased ceramide concentrations promoted differentiation of CD4 + regulatory T cells, but also negatively interfered with cytotoxic activity of CD8 + T cells, which was improved by elevated ceramide concentrations (98).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using T cell-specific acid sphingomyelinase-or acid ceramidase-deficient mice revealed that T cell-specific ablation of acid sphingomyelinase resulted in reduced ceramide levels in T cells and an impairment of T cell responses, whereas T cell specific deletion of the acid ceramidase elevated T cell activation (98). Decreased ceramide concentrations promoted differentiation of CD4 + regulatory T cells, but also negatively interfered with cytotoxic activity of CD8 + T cells, which was improved by elevated ceramide concentrations (98).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
“…A recent study using T cell-specific acid sphingomyelinase-or acid ceramidase-deficient mice revealed that T cell-specific ablation of acid sphingomyelinase resulted in reduced ceramide levels in T cells and an impairment of T cell responses, whereas T cell specific deletion of the acid ceramidase elevated T cell activation (98). Decreased ceramide concentrations promoted differentiation of CD4 + regulatory T cells, but also negatively interfered with cytotoxic activity of CD8 + T cells, which was improved by elevated ceramide concentrations (98). The studies also linked the T cell receptor (TCR/CD3) complex to ceramide-enriched membrane domains, since ceramide co-localized with the TCR/ CD3 complex forming an immune synapse in stimulated T cells, an event that seems to regulate the strength of TCR/CD3 signaling (99).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
“…Sphingolipids and their metabolic derivatives are involved in regulating processes including apoptosis and autophagy (13,14). The metabolism of sphingolipids also plays a role in the interactions between tumor cells and the immune system, influencing tumor cell behavior and the functionality of immune responses (15)(16)(17). Regulation of these metabolic pathways may reveal new therapeutic strategies for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%